Concordance of c‐kit Mutational Status in Matched Primary and Metastatic Cutaneous Canine Mast Cell Tumors at Baseline. (26th December 2013) - Marconato, L.; Zorzan, E.; Giantin, M.; Di Palma, S.; Cancedda, S.; Dacasto, M.
<x xml:space="preserve">Abstract</x> Background Mutation analysis of proto‐oncogene c‐kit (c‐kit) is advisable before starting treatment with tyrosine kinase inhibitors in dogs with mast cell tumor (MCT), including those with metastatic disease. Testing is usually performed on primary tumors, assuming that c‐kit mutation status does not change in metastasis. Hypothesis/Objectives To give an insight into the mutational processes and to make a recommendation on the use of c‐kit mutational analysis in the clinical setting. Animals Twenty‐one client‐owned dogs with metastatic MCT. Methods Dogs undergoing resection or biopsy for both primary and matched metastatic MCT were prospectively enrolled. Total RNA or DNA was extracted from primary MCT and corresponding metastases. Exons 8, 9, and 11 were amplified by PCR and sequenced. Genetic features between primary MCT and metastases were compared. Their correlation with clinicopathologic features was investigated. Results Concordance (mutated or wild‐type) of mutational status, evaluable in 21 primary and matched metastatic (20 nodal and 1 splenic) MCTs, was 100%. Three new c‐kit mutations were identified. No significant correlation was detected between c‐kit mutation and clinicopathologic features. Conclusions and Clinical Importance Proto‐oncogene c‐kit mutational status is conserved between any primary and its matched secondary tumor, suggesting that both can be used for c‐kit mutational testing. Targeted therapies might be also used to treat metastatic disease.